Associations of echocardiographic features with stroke in those without atrial fibrillation. (26th February 2019) - Johansen, Michelle C.; Lin, Michelle; Nazarian, Saman; Gottesman, Rebecca F.
Abstract : Objective: To determine the associations between transthoracic echocardiogram (TTE) cardiac structure/function measures and cardioembolic stroke (CES) and new-onset atrial fibrillation (AF) in patients without known AF. Methods: Inpatients at a single institution (2013–2015) with imaging-confirmed ischemic stroke, no AF, and TTE within the 1st week were included. TTE structure/function variables were abstracted. Stroke subtype (CES vs other) was defined according to Trial of Org 10172 in Acute Stroke Treatment, blinded to TTE results. New AF was defined as any duration of AF on ECG, telemetry, or event monitor. Separate multivariable logistic regression models defined associations between CES or new-onset AF and TTE measures, adjusting for demographic and vascular risk factors. Results: Of 322 participants (mean age 60 years), 55% were male and 56% African American. In adjusted models (odds ratio, 95% confidence interval), odds of CES increased per 0.1 cm increase in left atrial (LA) systolic diameter (1.06, 1.02–1.11), 1 cm/s in mitral E point velocity (1.03, 1.02–1.05), with presence of mitral valve dysfunction (3.78, 1.42–10.02), and with wall motion abnormality (2.00, 1.13–3.55). As ejection fraction increased (per 10%), odds of CES decreased (0.65, 0.53–0.79). New-onset AF was also associated with increasing LA systolic diameter (1.13, 1.04–1.22). Conclusions: Cardiac structural changes independent of AF and detectable on TTE may be on the CES causal pathway. Confirming these results could have implications for future use of TTE and decisions about antithrombotic vs anticoagulant treatment.